Korelasi Pemanfaatan Media Pembelajaran Digital dengan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di SMPN 4 Payakumbuh - Faizatur Rafi’ah; Zulfani Sesmiarni (Lembaga Yasin AlSys, 2026)
The use of digital learning media in Islamic Religious Education (PAI) instruction has received considerable attention in various studies, but research specifically analysing its relationship with PAI learning outcomes in schools implementing digital classes remains relatively limited. This study aimed to analyse the relationship between the use of digital learning media and PAI learning outcomes among students in the Grade VIII Digital Class at SMP Negeri 4 Payakumbuh. This study employed a quantitative approach with a correlational design. The participants comprised 95 students selected using total sampling. Data were collected through a questionnaire to measure the use of digital learning media and documentation of students’ PAI learning outcome scores. The data were analysed using descriptive statistics, prerequisite analysis tests, Spearman’s rank correlation, and simple linear regression with the assistance of IBM SPSS Statistics version 27. The results showed that the use of digital learning media was classified as good but was not significantly related to PAI learning outcomes. This was indicated by a correlation coefficient of 0.073 with a significance value of 0.481 (p > 0.05) and an R-squared value of 0.000, indicating that the use of digital learning media did not contribute to the variation in students’ learning outcomes. These findings confirm that a good level of digital media use is not directly associated with improved PAI learning outcomes because learning outcomes may be influenced by various other factors. This study enriches the literature on digital learning, particularly regarding the relationship between digital media use and PAI learning outcomes. The practical implication is that teachers need to integrate digital media with interactive and student-centred learning strategies, while future research should examine other factors related to PAI learning outcomes.